Immigration ethics: creating flourishing, just, and sustainable societies in a world of limits - Phillips, Addison, author; Cafaro, Philip, advisor; Shockley, Ken, committee member; Shulman, Steven, committee member; Rolston, Holmes, 1932-2025, committee member (Colorado State University. Libraries, 2018)
Most political liberals and academics hold that the proper ethical stance on immigration is one of expansive policies or even open borders. It is assumed that it is unjust to limit the movement of humans who are merely attempting to improve their lot in life by seeking to make an honest living in a new country. This thesis argues that a considered ethical view on immigration in our overpopulated and environmentally overexploited world must take the ethical import of limits seriously. In the first chapter, I argue that the right of a nation's citizens to exercise self-determination and pursue the creation of a flourishing society justifies limiting immigration to the degree that is required to secure various societal goods necessary to a flourishing society, such as the maintenance of mutual regard and a robust welfare state. In the second chapter, I argue that present ecological, economic, and social circumstances demand that developed nations exercise that right and limit immigration from the developing world, due to significant and pressing threats to their near and long-term prospects for flourishing. Mass immigration will never solve the issues the developing world currently faces, but it sends the false signal that it will solve these issues and fails to signal to developing nations the cost of their often extremely high fertility rates. Meanwhile, mass immigration burns financial and political capital in the developed world that should be spent on sustainable development aid and family planning services. Finally, I provide a detailed rebuttal of a potential counterargument that the rights of immigrants overrule considerations about limits and flourishing, arguing that the present regime of national parks and protected natural areas provides a precedent for the type of limits I propose.
Keywords: immigration; rights; sustainability; limits; flourishing; self-determination